2009
DOI: 10.1111/j.1478-3231.2008.01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative transporter pathways in patients with untreated early‐stage and late‐stage primary biliary cirrhosis

Abstract: The hepatic expression of multidrug-resistance protein 4 was enhanced in patients with untreated PBC at all stages. However, the hepatic expression of multidrug-resistance protein 2 and multidrug-resistance protein 3 was enhanced only in early-stage patients. The lack of upregulation of these proteins might contribute to the progression of PBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC. 149,190,193,194 Consistent with the literature findings, data from our laboratory indicated that MRP1 protein was expressed in liver tissue from a patient with PBC (Figure 1). Interestingly, our findings suggest that MRP1 was expressed primarily in the inflamed tissues in macrophages around the hepatocytes in PBC.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC. 149,190,193,194 Consistent with the literature findings, data from our laboratory indicated that MRP1 protein was expressed in liver tissue from a patient with PBC (Figure 1). Interestingly, our findings suggest that MRP1 was expressed primarily in the inflamed tissues in macrophages around the hepatocytes in PBC.…”
Section: Introductionsupporting
confidence: 89%
“…189 Interestingly, it was reported that these alterations may be related to the adaptation of transporters, and that expression patterns may change from early to late stage PBC. 190,193 In addition to the changes in expression, the localization of MRP2 was altered in PBC stage III. 191 MRP1 and OST α/β, which are not expressed or expressed at low levels in normal hepatocytes, are upregulated in patients with PBC.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cirrhotic liver parenchyma may have reduced enhancement in the hepatobiliary phase relative to non‐cirrhotic parenchyma due to an impaired uptake and transport mechanism for Gd‐EOB‐DTPA. We have previously described the expression of MRP2 and the downregulation of hepatic MRP2 mRNA levels in LC‐PBC …”
Section: Discussionmentioning
confidence: 99%
“…In response, hepatobiliary transporters are expressed to prevent bile acid accumulation in hepatocytes . We previously described that the lack of adaptation to the upregulation of hepatobiliary transporters may be related to PBC progression …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation